PENGARUH KOMPENSASI DAN MOTIVASI KERJA KARYAWAN TERHADAP KINERJA PERUSAHAAN (Studi Kasus Pada PT. Wahana Ottomitra Multiartha Tbk) - Imam Syatoto (Universitas Pamulang, 2017)
ABSTRACT The purpose of this case study is to examine the influence of compensation and motivation to company performance. Grand Theory is human need theory based on Abraham Maslow. Middle Theory is compensation and motivation theory based on Dessler and and David McClelland. Application Theory is the influence of compensation and motivation to company performance based on Isnarijanto. The population of this research is an information techonology information company with 100 employess consists of 80 responden as the applicable sample. There are two independent variables included in this research; they are compensation and motivation, and company performance is dependent variable. The data analysis for hypothesis examination is proceeded by SPSS 16.0 application using multivariate regression and correlations. The result of this research indicates that compensation and motivation have positive and significant influence amount 69,8%along with strong correlation to the positive direction to company performance partially and simultaneously. However, compensation and motivation do not only become variables which haveinfluence and strong correlations to company performance, but also there are 30,2% of other variables contribute to the company performance and open for the next researches. The multiple regression model is Y = a + b1X1 + b2X2 In conclusion, the study case in PT Wahana Ottomitra Multiartha has indicated that company performance could be increased by giving the proper compensation and high motivation from the employees.